Integration of Indonesian Language and Literature Learning in the Merdeka Curriculum: A Holistic Approach to Enhancing Literacy and Cultural Appreciation in Secondary Schools - Anum, Adelina; Eripuddin, Eripuddin; Rahayu , Pipit; Irmawati , Lisa (CV. Tripe Konsultan, 2025)
This study examined the integration of Indonesian language and literature learning within the context of Merdeka Curriculum implementation at the secondary school level as a strategy to strengthen students’ literacy and cultural appreciation. The main objective of this research is to understand the extent to which an integrative approach can improve the quality of learning that is not only cognitively oriented but also affective and cultural in nature. The subjects of this research consist of 20 scholarly articles selected through purposive sampling based on their relevance to the topic and the publication period between 2015 and 2025. The characteristics of the literature encompass perspectives on educational policy, pedagogical strategies, and empirical studies involving junior and senior high school students from diverse socio-cultural backgrounds. This study employs a qualitative approach using a library research method, with documentation techniques for data collection and thematic analysis to identify patterns, trends, and conceptual contributions from each source. The findings indicate that integrating language and literature learning significantly enhances students' literacy skills, broadens their cultural insights, and creates more reflective and meaningful learning experiences. Learning strategies that combine literary texts and language practice foster students' critical thinking, empathy, and appreciation of literature as well as real-life contexts. These findings confirm that the integration of language and literature not only substantively strengthens the implementation of the Merdeka Curriculum but also contributes to the formation of the Pancasila Student Profile. As an implication, this approach needs to be further developed through teacher training, the provision of contextual learning media, and educational policies that support holistic and transformative teaching practices.